Development of the HIV360 international core set of outcome measures for adults living with HIV: A consensus process. Issue 6 (28th December 2021) - Marques‐Gomes, João; Salt, Matthew J.; Pereira‐Neto, Rita; Barteldes, Franca S.; Gouveia‐Barros, Vera; Carvalho, Alexandre; d'Arminio‐Monforte, Antonella; De‐la‐Torre‐Rosas, Alethse; Harris, Amy; Esteves, Catarina; Maor, Carcom; Mora, Cristina; et al.
Abstract: Objectives: HIV outcomes centre primarily around clinical markers with limited focus on patient‐reported outcomes. With a global trend towards capturing the outcomes that matter most to patients, there is agreement that standardizing the definition of value in HIV care is key to their incorporation. This study aims to address the lack of routine, standardized data in HIV care. Methods: An international working group (WG) of 37 experts and patients, and a steering group (SG) of 18 experts were convened from 14 countries. The project team (PT) identified outcomes by conducting a literature review, screening 1979 articles and reviewing the full texts of 547 of these articles. Semi‐structured interviews and advisory groups were performed with the WG, SG and people living with HIV to add to the list of potentially relevant outcomes. The WG voted via a modified Delphi process – informed by six Zoom calls – to establish a core set of outcomes for use in clinical practice. Results: From 156 identified outcomes, consensus was reached to include three patient‐reported outcomes, four clinician‐reported measures and one administratively reported outcome; standardized measures were included. The WG also reached agreement to measure 22 risk‐adjustment variables. This outcome set can be applied to any person living with HIV aged > 18 years. Conclusions: Adoption of the HIV360 outcome set will enable healthcare providers to record, compare and integrate standardized metrics across treatment sites to drive quality improvement in HIV care.